Fragility syndrome: determinant factors in institutionalized elderly - Silva, Daniela Fonseca; Alves, Roberta Almeida; Pesavento, Thomas Fernando Coelho; Vilarinho, Manoela; Lombardi Junior, Império; Agner, Vania Fernanda Clemente (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The aim of the study was to evaluate the frailty syndrome in residents of a Long-Term Care Facility for the Elderly. A cross-sectional study was carried out on 24 subjects over the age of 60 years. For the screening of frailty syndrome, the criteria of the Cardiovascular Study were used, which classifies the subjects into fragile, pre-fragile and non-fragile according to five criteria: decreased handgrip strength; self-reported fatigue; decrease in walking speed; unintentional weight loss; and low level of physical activity. The average age of the population studied was 81.13 years, with 54.20% being female. Among the elderly, 83.33% were frail, 12.50% were pre-frail and 4.17% were not frail. Elderly people over 80 years old had a higher incidence of frailty when compared to those aged 60 - 79 years, with 85.7% and 80%, respectively. Since 66.67% of the elderly had decreased handgrip muscle strength, 37.50% reported fatigue, 41.67% demonstrated decreased gait speed, 12.50% unintentional weight loss and 87.50% were physically inactive. We identified a high prevalence of DES among the elderly residing in the institution studied, thus reinforcing the importance of early screening for frailty in institutionalized elderly.